Regulation of extracellular matrix in patients with Q-wave myocardial infarction after thrombolytic therapy - Syvolap, V. D.; Kyselov, S. M.; Сиволап, Віктор Денисович; Кисельов, Сергій Михайлович; Сыволап, В. Д.; Киселев, С. М. (Запорізький державний медичний університет, 2014)
Aims. In order to study the levels of matrix metalloproteinase-9, tissue inhibitor of metalloproteinase-1, intracardiac hemodynamics, frequency of acute cardiac aneurysm development in patients with Q-wave myocardial infarction after thrombolysis, 74 patients were examined. Methods and results. All participants underwent clinical and laboratory examination, echocardiography, determination of serum levels of matrix metalloproteinase-9 and tissue inhibitor of metalloproteinase-1. Conclusion. Patients, who got thrombolysis in 6 to 12 hours period, had excessive activation of the proteolysis system on the background of relative defi cit of tissue inhibitor of metalloproteinase-1, the prevalence of dilatation and restrictive diastolic dysfunction, cardiac aneurysm was detected frequently and thrombogenic potential was higher. З метою вивчення рівнів матриксної металопротеїнази-9, тканинного інгібітора металопротеїнази-1, стану внутрішньосерцевої гемодинаміки, частоти виникнення гострої післяінфарктної аневризми серця у хворих на Q-інфаркт міокарда після тромболізису обстежено 74 хворих. Усім пацієнтам проведено клініко-лабораторне обстеження, ехокардіографію, визначено сироваткові рівні матриксної металопротеїнази-9 та тканинного інгібітора металопротеїнази-1. У хворих, яким проводили тромболізис у строки від 6 до 12 годин, встановили надмірну активацію системи протеолізу на тлі відносного дефіциту тканинного інгібітора металопротеїнази-1, перевагу процесів дилатації та рестриктивний тип діастолічної дисфункції лівого шлуночка, частіше виявляли аневризму серця та визначили більший тромбогенний потенціал. С целью изучения уровней матриксной металлопротеиназы-9, тканевого ингибитора металлопротеиназы-1, состояния внутрисердечной гемодинамики, частоты возникновения острой постинфарктной аневризмы сердца у больных Q-инфарктом миокарда после тромболизиса обследовано 74 больных. Всем пациентам проведено клинико-лабораторное обследование, эхокардиографию, определены сывороточные уровни матриксной металлопротеиназы-9 и тканевого ингибитора металлопротеиназы-1. У больных, которым проводили тромболизис в сроки от 6 до 12 часов, установили чрезмерную активацию системы протеолиза на фоне относительного дефицита тканевого ингибитора металлопротеиназы-1, преобладание дилатации и рестриктивный тип диастолической дисфункции левого желудочка, чаще обнаруживали аневризму сердца и определили больший тромбогенный потенциал.
Регуляція екстрацелюлярного матриксу у хворих на Q-інфаркт міокарда після тромболітичної терапії
Регуляция экстрацелюлярного матрикса у больных Q-инфарктом миокарда после тромболитической терапии
Keywords: matrix metalloproteinase; myocardial infarction; heart aneurysm; матриксна металопротеїназа; інфаркт міокарда; аневризма серця; матриксная металлопротеиназа; инфаркт миокарда; аневризма сердца